Developing Digital Collections in an Open Access Environment with Intellectual Property Challenges: Mengembangkan Koleksi Digital dalam Lingkungan Akses Terbuka dengan Tantangan Hak Kekayaan Intelektual - Ahmed Kadhim Hantoush (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The open access movement has transformed scholarly communication by promoting unrestricted access to scientific knowledge and research outputs. Academic libraries play a crucial role in managing and providing access to digital resources within this evolving information ecosystem. Specific Background As open access materials continue to expand, libraries are increasingly integrating these resources into their digital collections while adapting traditional collection development strategies. Knowledge Gap Despite these developments, many libraries face challenges in balancing open access dissemination with intellectual property protection and copyright compliance, creating uncertainty in digital collection management practices. Aims This study examines how academic libraries incorporate open access resources into digital collections while addressing intellectual property and copyright issues. Results The findings indicate that libraries must adopt new evaluation, licensing, and management strategies to integrate open access materials effectively while ensuring legal compliance and ethical use of information resources. Novelty The study highlights the relationship between open access adoption and intellectual property challenges in digital collection development within academic libraries. Implications The results provide insights for libraries seeking to develop sustainable digital collection strategies that support open access while maintaining responsible intellectual property management. Keywords: Open Access, Digital Collections, Academic Libraries, Intellectual Property, Scholarly Communication Key Findings Highlights Academic libraries increasingly integrate open access materials into digital collection strategies. Intellectual property and copyright regulations remain central challenges in open access environments. Libraries require structured policies to manage licensing and ensure lawful dissemination of digital resources.